Bandung City as a Smart City Model: Navigating Policies, Challenges, and Innovative Solutions - Naomi Glori Natalia; Anneke Zehan Puspita Sari; Ratu Wulan Nur Cahya; Ivan Darmawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
The global surge in urbanization has imposed a pressing need for cities to adapt and progress. Amidst this tide of transformation, Bandung, Indonesia, emerges as a guiding light, striving to embody the essence of the Smart City concept. This article conducts an in-depth evaluation of Bandung's journey towards becoming a Smart City, scrutinizing its advancements against the backdrop of six pivotal indicators.At the core of this evaluation lies a deep understanding of the Smart City essence, where the fusion of Information and Communication Technology catalyzes a revolution in urban living. Bandung's initiation into the realm of Smart City, commencing in 2013, marks the onset of a comprehensive expedition characterized by innovation, community engagement, and a commitment to sustainability. The pillars of Smart Economy, Smart People, Smart Governance, Smart Mobility, Smart Living, and Smart Environment serve as the defining elements shaping Bandung's evolutionary path. The city thrives on the vibrancy of its educational institutions and the burgeoning creative industries within its bounds. However, persistent challenges in infrastructure and accessibility underscore the crucial need for substantial investment in digital infrastructure and initiatives to enhance digital literacy. Bandung's aspiration for a smarter future necessitates holistic strategies that not only address these challenges but also harness the city's technological prowess and engage the community in a collaborative approach. This analysis endeavors to act as a guiding compass, charting Bandung's trajectory towards a fully integrated and sustainable Smart City paradigm.